Strategi Pembelajaran Kontekstual Berbasis Teknologi Digital untuk Penguatan Internalisasi Nilai Keislaman di SMP & SMA: Penelitian - Nurhanudin; Eti Nurhayati; Anda Juanda (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Islamic Religious Education (PAI) in the digital era faces great challenges and opportunities in transforming learning approaches that are adaptive, interesting and contextual. This research aims to examine forms of innovation in technology-based PAI learning and how these innovations can improve students' religious understanding, attitudes and practices. The method used is library research with a qualitative approach. The research results show that the application of technology such as the Learning Management System (LMS), Islamic mobile applications, social media, and educational games based on Islamic values ​​can increase student involvement and strengthen the internalization of values. This article recommends the integration of a collaborative digital curriculum and training of PAI teachers in mastering technology to create a relevant and competitive religious education ecosystem.